Effect of Febuxostat on Ambulatory Blood Pressure in Subjects With Hyperuricemia and Hypertension: A Phase 2 Randomized Placebo‐Controlled Study. Issue 11 (4th November 2017) - Gunawardhana, Lhanoo; McLean, Lachy; Punzi, Henry A.; Hunt, Barbara; Palmer, Robert N.; Whelton, Andrew; Feig, Daniel I.
Abstract : Background: Hyperuricemia is associated with hypertension, with elevated serum uric acid levels postulated to have a causal role in the development of hypertension. Consequently, serum uric acid reduction may help lower blood pressure (BP). A Phase 2, double‐blind, placebo‐controlled trial was conducted to assess the potential BP‐lowering effects of the xanthine oxidase inhibitor febuxostat in subjects with hypertension and hyperuricemia (serum uric acid ≥0.42 mmol/L [≥7.0 mg/dL]). Methods and Results: Subjects (n=121) were randomized 1:1 to febuxostat 80 mg once daily or to placebo. The primary end point was change from baseline to Week 6 in 24‐hour mean ambulatory systolic BP (SBP). Additional end points included the following: change from baseline to Week 3 in 24‐hour mean SBP and changes from baseline to Weeks 3 and 6 in 24‐hour mean ambulatory diastolic BP, serum uric acid, mean daytime and nighttime ambulatory SBP/diastolic BP, and clinic SBP/diastolic BP. For the overall study population, there were no significant differences between febuxostat and placebo for changes from baseline to Weeks 3 or 6 in ambulatory, daytime or nighttime, or clinic SBP or diastolic BP. However, in a preplanned subgroup analysis, there was a significant decrease in SBP from baseline to Week 6 in subjects with normal renal function (estimated glomerular filtration rate ≥90 mL/min) treated with febuxostat versus placebo; least squares mean difference, −6.7; 95% confidence interval −13.3 to −0.0; P =0.049. Conclusions: This study suggests that febuxostat may lower BP in hyperuricemic patients with hypertension and normal renal function; further studies should be conducted to confirm this finding. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01496469.